Digital Asset Management in the Communication of Product Promotional Activities - Chimakurthi, Venkata Naga Satya Surendra (Asian Business Review, 2020)
Digital asset management (DAM) is utilized in various scenarios and for a variety of technological goals. This study investigates the implications of digital asset management systems on product promotion, advertising, and marketing, as this is a new application area for the technology in question. When it comes to handling electronic content, digital asset management (DAM) is utilized in various scenarios for a variety of technological goals. A conceptual framework for describing promotional processes in the worlds of information technology and promotional communication logistics is presented in this paper. It is explained in the study how a coherent DAM system helps to advertise agencies to execute more work with fewer employees by providing speed to market, productivity savings, enhanced agency, and client revenues, secure client branding. Readers will learn how to deal with fundamental challenges such as file-naming criteria, load balancing, and maintaining cultural buy-in inside the organization from reading this article. Grounded on the findings of the review of related literature, the potential benefits of digital asset management in this context are discussed. An explanatory study is used to scrutinize the anticipated advantages. The description of marketing supply networks yields fresh insights into managing supply chain operations.